2017
DOI: 10.1093/mnras/stx560
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical friction in the primordial neutrino sea

Abstract: Standard big bang cosmology predicts a cosmic neutrino background at T ν 1.95 K. Given the current neutrino oscillation measurements, we know most neutrinos move at large, but non-relativistic, velocities. Therefore, dark matter haloes moving in the sea of primordial neutrinos form a neutrino wake behind them, which would slow them down, due to the effect of dynamical friction. In this paper, we quantify this effect for realistic haloes, in the context of the halo model of structure formation, and show that it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 45 publications
3
30
1
Order By: Relevance
“…We can use either the CDM or the neutrino rest frame to compute the observable quantities as long as we express the fields in the same coordinate frame. As we see, the relative bulk flow of the neutrino and CDM fluids leads to asymmetric matter distribution in the total matter density field along the direction of the CDM-neutrino relative velocity [16][17][18][19].…”
Section: Relative Velocitymentioning
confidence: 70%
See 1 more Smart Citation
“…We can use either the CDM or the neutrino rest frame to compute the observable quantities as long as we express the fields in the same coordinate frame. As we see, the relative bulk flow of the neutrino and CDM fluids leads to asymmetric matter distribution in the total matter density field along the direction of the CDM-neutrino relative velocity [16][17][18][19].…”
Section: Relative Velocitymentioning
confidence: 70%
“…The relative advection between the initial coherent CDM and neutrino density causes a dipole contribution to the local correlation of CDM and neutrinos [16]. On nonlinear scales, neutrinos become gravitationally focused into wakes as they flow over dark matter halos, further increasing the strength of the dipole clustering of neutrinos around high CDM density regions [17,18]. However, the computation of dipole correlation only uses the CDM-neutrino relative velocity direction and is affected by the halo-CDM or baryon-CDM relative flows [19].…”
Section: Introductionmentioning
confidence: 99%
“…One (practically) guaranteed background is from cosmic neutrinos, which will also have a relative velocity Zhu et al (2014); Inman et al (2015Inman et al ( , 2017 and dynamical friction Okoli et al (2017), although of course no SZE. The numbers we obtain may be compared to the prediction for neutrino dynamical friction of Okoli et al (2017) who found values of order 0.2 km/s and 1.5 kpc/h (depending on halo and neutrino properties) when averaged over 16 Mpc/h. Of course, the key differences are that neutrinos are collisionless and therefore not subject to hydrodynamic forces, but more importantly that the baryons can contribute significantly more to the matter density since Ω g Ω ν .…”
Section: Resultsmentioning
confidence: 99%
“…It is also worth considering what other effects may mimic or contaminate our results. One (practically) guaranteed background is from cosmic neutrinos, which will also have a relative velocity Zhu et al (2014); Inman et al (2015Inman et al ( , 2017 and dynamical friction Okoli et al (2017), although of course no SZE. The numbers we obtain may be compared to the prediction for neutrino dynamical friction of Okoli et al (2017) who found values of order 0.2 km/s and 1.5 kpc/h (depending on halo and neutrino properties) when averaged over 16 Mpc/h.…”
Section: Discussionmentioning
confidence: 99%
“…The relative velocity between relic neutrinos and dark matter at low redshifts leads to a neutrino wake, downstream of the dark matter haloes. This causes a dipole distortion of galaxy-galaxy lensing, detectable from cross-correlations between different galaxy populations and 21 cm intensity mapping experiments (Okoli et al, 2017;Zhu et al, 2014). High precision 21 cm lensing surveys (e.g.…”
Section: Theoretical Advancesmentioning
confidence: 99%